The Columbia guide to Central African literature in English since 1945 - Roscoe, Adrian A. (Columbia guides to literature since 1945., 2008)
"Columbia's guides to postwar African literature paint a unique portrait of the continent's rich and diverse literary traditions. This volume examines the rapid rise and growth of modern literature in the three postcolonial nations of Zimbabwe, Malawi, and Zambia. It tracks the multiple political and economic pressures that have shaped Central African writing since the end of World War II and reveals its authors' heroic efforts to keep their literary traditions alive in the face of extreme poverty and AIDS."--Jacket.